Keeping and breeding of exotic lizards - Panker, Máté (Animal welfare, Ethology and Housing Systems (AWETH), 2011)
The demand after unusual and exotic animals, which can be felt in our country, is increasing from year to year. The pet keepers are always looking for new, uncommon animals. When a new species enters the trade flow, we can often see that the demand is much greater than the current supply, because the indoor breeding and upholding technology of the species has not yet been solved. However, the dealers tries to meet the animal keeper’s needs with wild-caught specimens. This solution may yield the endangerment of the given race, its extinction on a long distance. Someones recognised the problem, and in case of snakes, it seems to be solved by using breeding systems. The technology is different in the instance of lizards, some of the species requires more area and light. Aim of this study was to review the breeding of exotic lizards in big quantities.